Novel calcium-sensing receptor cytoplasmic tail deletion mutation causing autosomal dominant hypocalcemia: molecular and clinical study - Obermannova, Barbora; Sumnik, Zdenek; Dusatkova, Petra; Cinek, Ondrej; Grant, Michael; Lebl, Jan; Hendy, Geoffrey N (European journal of endocrinology, 2016)
OBJECTIVE: Autosomal dominant hypocalcemia (ADH) is a rare disorder caused by activating mutations of the calcium-sensing receptor (CASR). The treatment of ADH patients with 1α-hydroxylated vitamin D derivatives can cause hypercalciuria leading to nephrocalcinosis. DESIGN AND METHODS: We studied a girl who presented with hypoparathyroidism and asymptomatic hypocalcemia at age 2.5 years. Mutations of CASR were investigated by DNA sequencing. Functional analyses of mutant and WT CASRs were done in transiently transfected human embryonic kidney (HEK293) cells. RESULTS: The proband and her father are heterozygous for an eight-nucleotide deletion c.2703_2710delCCTTGGAG in the CASR encoding the intracellular domain of the protein. Transient expression of CASR constructs in kidney cells in vitro suggested greater cell surface expression of the mutant receptor with a left-shifted extracellular calcium dose-response curve relative to that of the WT receptor consistent with gain of function. Initial treatment of the patient with calcitriol led to increased urinary calcium excretion. Evaluation for mosaicism in the paternal grandparents of the proband was negative. CONCLUSIONS: We describe a novel naturally occurring deletion mutation within the CASR that apparently arose de novo in the father of the ADH proband. Functional analysis suggests that the cytoplasmic tail of the CASR contains determinants that regulate the attenuation of signal transduction. Early molecular analysis of the CASR gene in patients with isolated idiopathic hypoparathyroidism is recommended because of its relevance to clinical outcome and treatment choice. In ADH patients, calcium supplementation and low-dose cholecalciferol avoids hypocalcemic symptoms without compromising renal function.
Keywords: Sequence Deletion; hyperkalciurie; sekvence nukleotidů; heterozygot; sekvenční delece; Male; Receptors, Calcium-Sensing; receptory "calcium-sensing"; Family; Child, Preschool; rodina; rodokmen; Hypercalciuria; Pedigree; Heterozygote; hypokalcemie; HEK293 buňky; Protein Structure, Tertiary; nesmyslný kodon; hypoparatyreóza; terciární struktura proteinů; Adult; HEK293 Cells; dospělí; mužské pohlaví; předškolní dítě; dominantní geny; cytoplazma; lidé; Cytoplasm; ženské pohlaví; Genes, Dominant; Humans; Codon, Nonsense; Base Sequence; Female; Hypoparathyroidism; Hypocalcemia